1991
DOI: 10.1007/bf01741333
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of growth suppression and modulation of the antigenic phenotype in human melanoma cells by the combination of recombinant human fibroblast and immune interferons

Abstract: Administration of interferon as a single therapeutic regimen in cancer patients with various neoplasias has had only limited efficacy in ameliorating the negative clinical course of their disease. In the present study, we have evaluated the effect of recombinant human fibroblast (IFN beta) and immune (IFN gamma) interferon, alone and in combination, on growth, differentiation and the expression of class I and II histocompatibility locus antigens (HLA) and melanoma-associated antigens on the human melanoma cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 38 publications
(42 reference statements)
0
18
0
Order By: Relevance
“…The blot was stripped and then reprobed with a 32 P-labeled GAPDH probe. FM516 is an SV40-immortalized normal melanocyte cell line (FM516-SV); WM35 is an early RGP primary melanoma cell line; WM278 is an early VGP primary melanoma cell line; WM239, FO-1, C8161, MeWo, 3S5 and 70W are metastatic melanoma cell lines; SK-MEL p53 mt is a metastatic melanoma cell line with a con®rmed mutant p53 genotype; and SK-MEL p53 wt is a metastatic melanoma cell line with a con®rmed wild-type p53 genotype having a mutant p53 gene by itself can prevent mda-7 expression, since MeWo and its two subclones, 3S5 displaying a reduction in metastatic competence and 70W exhibiting enhanced metastatic potential (Kerbel and Man, 1984;Graham et al, 1991), which contain one mutant and one wild-type p53 allele are readily inducible for mda-7 expression following IFN-b+MEZ treatment. These studies document de novo expression of mda-7 in cultured normal human melanocytes, as observed with patient-derived melanocytes, and they provide additional support for the idea that mda-7 may function as a negative regulator of melanoma progression (Jiang et al, 1995b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The blot was stripped and then reprobed with a 32 P-labeled GAPDH probe. FM516 is an SV40-immortalized normal melanocyte cell line (FM516-SV); WM35 is an early RGP primary melanoma cell line; WM278 is an early VGP primary melanoma cell line; WM239, FO-1, C8161, MeWo, 3S5 and 70W are metastatic melanoma cell lines; SK-MEL p53 mt is a metastatic melanoma cell line with a con®rmed mutant p53 genotype; and SK-MEL p53 wt is a metastatic melanoma cell line with a con®rmed wild-type p53 genotype having a mutant p53 gene by itself can prevent mda-7 expression, since MeWo and its two subclones, 3S5 displaying a reduction in metastatic competence and 70W exhibiting enhanced metastatic potential (Kerbel and Man, 1984;Graham et al, 1991), which contain one mutant and one wild-type p53 allele are readily inducible for mda-7 expression following IFN-b+MEZ treatment. These studies document de novo expression of mda-7 in cultured normal human melanocytes, as observed with patient-derived melanocytes, and they provide additional support for the idea that mda-7 may function as a negative regulator of melanoma progression (Jiang et al, 1995b).…”
Section: Resultsmentioning
confidence: 99%
“…Treatment of human melanoma cells with IFNb+MEZ results in profound physiological changes, including an irreversible loss in proliferative potential, suppression of oncogenic potential in athymic nude mice, altered cell surface antigenicity, temporal alterations in gene expression and induction of terminal di erentiation (Fisher et al, 1985;Graham et al, 1991;Jiang et al, , 1994Jiang et al, , 1995aJiang et al, ,b, 2000Huang et al, 1999a,b;Kang et al, 2001;Leszczyniecka et al, 2001). To obtain insights into this process we have begun to de®ne the spectrum of gene expression changes occurring as a consequence of this combination treatment in human melanoma cells using several molecular approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HO-1 and MeWo are established human melanotic melanoma cell lines and FO-1 is an established human amelanotic melanoma cell line isolated from separate patient-derived metastatic lesions (Giovanella et al, 1976;Kerbel et al, 1994;Fisher et al, 1985;Graham et al, 1991). WM35 was derived from an RGP primary human melanoma (Herlyn, 1990).…”
Section: Cell Lines and Culture Conditionsmentioning
confidence: 99%
“…The other is the pathological process of neoplastic transformation characterized by uncontrolled proliferation and de-differentiation. Treatment of HO-1 metastatic human melanoma cells with fibroblast interferon (IFN-␤) 1 and the protein kinase C activator mezerein (MEZ) induces irreversible growth arrest and terminal differentiation characterized by changes in cell morphology, increase in melanin synthesis, modifications in gene expression, and alterations in surface antigen expression (1)(2)(3)(4)(5). Replicative or cellular senescence, a process leading to irreversible arrest of cell division, was first described in cultures of human fibroblasts that lost the ability to divide upon continuous subcultures (6).…”
mentioning
confidence: 99%